Successful Treatment of Pregnant and Postpartum Women With Severe COVID-19 Associated Acute Respiratory Distress Syndrome With Extracorporeal Membrane Oxygenation. Issue 2 (February 2021) - Barrantes, Jairo H.; Ortoleva, Jamel; O'Neil, Erika R.; Suarez, Erik E.; Beth Larson, Sharon; Rali, Aniket S.; Agerstrand, Cara; Grazioli, Lorenzo; Chatterjee, Subhasis; Anders, Marc
Abstract : There are limited data on the use of extracorporeal membrane oxygenation (ECMO) for pregnant and peripartum women with COVID-19 associated acute respiratory distress syndrome (ARDS). Pregnant women may exhibit more severe infections with COVID-19, requiring intensive care. We supported nine pregnant or peripartum women with COVID-19 ARDS with ECMO, all surviving and suffering no major complications from ECMO. Our case series demonstrates high-maternal survival rates with ECMO support in the management of COVID-19 associated severe ARDS, highlighting that these pregnant and postpartum patients should be supported with ECMO during this pandemic.